Histopathological Observation Of Infestation Of Dactylogyrusspp. In Grass Carp, Ctenopharyngodonidella (International Journal of Food and Nutritional Sciences, 2023)
The present investigation was undertaken the parasitic effect ofmonogeneantrematode,Dactylogyrus spp. caused histopathological alteration in grass carp, Ctenopharyngodonidella. There were only symptomatic samples of diseased fishes comprised of fingerlings and adults of C. idella collected from different ponds of Darbhanga. In clinical test infested fish showed gill pale in colour and had haemorrhagic and inflamed areas at the sites of parasite attachments.The significant histopathological lesions and changes were observed in the gills where the parasites were found attached to the lamellar tissues causing local erosions of the epithelium and hyperplasia of the secondary lamellar epithelium and fusion of adjacent secondary lamellae, vascular congestion leading to aneurysm besides, clumbing of the tips in secondary lamellae, congested gill showed accumulation of blood leading to swelling hypertrophy in secondary lamellae, autolysis of epithelium and secondary lamellae and severe edema and necrosis were observed in gill of grass carp.Except gill no changes were noticed in other organs of the infested fish. The growth retardation was observed in affected fish. The histopathological analysis for parasites in fish will be useful tool for fish health management.